Madrasah Reposition in Building Community Trust in Covid-19 Era Disruption - Ahmad Salim; Muh Mustakim (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
The advancement of information systems is an opportunity and a challenge as well as for Islamic educational institutions. One of them is a madrasah. If madrasah does not respond appropriately and wisely to this progress, madrasah will be left behind and even abandoned. Thus, in simple terms the era of